(untitled) (Texas Journal of Multidisciplinary Studies, 2022)
This article is about Hitler, the organization that played a key role in training German youth to be nationalists and racists. The main reason for covering this topic is to reveal that nationalism is very dangerous and that it can lead to bad consequences in the long run.